Environmental management regarding resource recovery in Malaysia - Masoud Aghajani Mir,; Sanaz Saheri,; Noor Ezlin Ahmad Basri,; Rawshan Ara Begum,; Noor Zalina Mahmood, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Waste disposal is a global problem contributing to the ongoing climate change due to large emissions of greenhouse gases. So, by using a waste material as a resource instead of land filling, the greenhouse gas emissions from landfills will be reduced. Also, Waste material can be used for waste incineration with energy recovery, thus decreasing the greenhouse gas emission from energy utilization by changing from fossil fuels to a partly renewable fuel. The production of Refuse Derived Fuels (RDF) involves the mechanical processing of household waste using screens, shredders and separators to recover recyclable materials and to produce a combustible product Regarding Resource Recovery Center/Waste to Energy (RRC/WtE) Facility in Malaysia that located in Semenyih. This System involves the removal of inert and compostable materials followed by pulverization to produce a feedstock which be incinerated in power stations. The purpose of this study is to evaluate and forecasting of the number of these facilities that Kuala Lumpur will need regarding to potential of Municipal Solid Waste (MSW) generation and Refuse Derive Fuel that will be produce from that in the future. This plant can produce average 7.5 MWh electricity from 700 tons MSW or 200 ton RDF per day that approximately is used 1.8 MWh per day inside the pant, and it can sell around 5.7 MWh daily. Kuala Lumpur will generate around 7713 tons MSW per day, and it is able to produce 2466 ton RDF per day. Regarding to potential of MSW and RDF generation by 2020 in Kuala Lumpur it will need around 11 plants to treatment of MSW that this number of plant are able to produce around 62.7 MWh electricity per day